Metathesis Phenomenon in Al-Qur'an - Kafin Jaladri; Syamsul Hadi (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2023)
Purpose: This study examines metathesis in the Quran for morphological changes in its lexicon. Metathesisâ€”reordering phonemes inside wordsâ€”illuminates the evolution of Arabic and the Quran's exegesis. This study identifies and analyzes Quranic metathesis events to determine their effects on understanding and translation accuracy. Design/ methods/approach: Employing a rigorous qualitative methodology, this study adopts a descriptive analytical approach. It scrutinizes a selection of Quranic words that have undergone metathesis, juxtaposing their original and altered phonemic structures. The inquiry is anchored in primary sources, predominantly the Quranic text, and is further bolstered by an array of exegetical and linguistic scholarly works. Findings: The findings from this investigation reveal that metathesis in the Quran transcends mere linguistic curiosity, bearing significant ramifications for theological discourse and hermeneutic practices. It is observed that these phonemic transformations can subtly, yet substantially, influence the semantic and interpretative dimensions of Quranic verses, notwithstanding the preservation of their intrinsic syntactic integrity in a wider linguistic context. Research implications: Â Contributing to the domain of Quranic linguistics, this research underscores the indispensability of linguistic considerations in theological scholarship and Quranic interpretation. It unveils novel perspectives on the intricate interplay between language and meaning within the Quran, highlighting the critical role of nuanced linguistic analysis in the exegesis of sacred texts. Ultimately, the study furnishes profound insights into the symbiotic relationship among language, semantics, and context inherent in the Quran.